Mesozoic tectonic transition of the northeastern North China Craton: Evidence from adakitic rocks in southeastern Jilin Province, China. Issue 1 (2nd January 2023) - Chen, Yu-Song; Liu, Zheng-Hong; Guan, Qing-Bin; Wan, Le; Liu, Jin; Gao, Tian-Yu
ABSTRACT: Chronological and geochemical studies of adakites and adakitic rocks are important in understanding the tectonic evolution and geodynamic processes. We present new zircon U–Pb ages, Hf isotope, and geochemical analyses of adakitic rocks exposed in the Baishan area, southeastern Jilin Province, China. These new ages, together with existing age data, indicate that adakitic magmatism in southeastern Jilin Province can be subdivided into four stages: Early–Middle Triassic (251–235 Ma), Late Triassic (221–219 Ma), late Early–early Late Jurassic (176–156 Ma), and Early Cretaceous (ca. 130 Ma). Early–Middle Triassic adakitic rocks occur in a nearly E–W-trending belt within the northern margin of the northeastern North China Craton, indicating a compressional tectonic setting caused by the scissor-like closure of the Paleo-Asian Ocean from west to east. Late Triassic adakitic rocks occur in the Tonghua area and formed in an extensional setting caused by delamination after subduction and collision between the Yangtze Craton and NCC. Late Early–early Late Jurassic adakitic rocks occur in the Baishan and Kaiyuan areas and originated from partial melting of thickened lower crust in a compressional setting related to subduction of the Paleo-Pacific Plate. Early Cretaceous adakitic rocks occur in the Baishan area and were derived from partial melting of thickened lower crust above the subduction zone and delaminated lower crust, indicating that the subducting Paleo-Pacific Plate retreated to the eastern part of southern Jilin Province during the Early Cretaceous (ca. 130 Ma) and that the tectonic setting of the northeastern part of the NCC changed from compression to extension, starting in the east and progressing westward. In summary, the northeastern part of the NCC has been affected by a series of tectonic events during the Mesozoic, such as the closure of the Paleo-Asian Ocean, the collision between the NCC and YC, and the subduction of the Paleo-Pacific Plate. GRAPHICAL ABSTRACT: uf0001